The date palm sector in Egypt - Riad M. (Le palmier dattier dans l'agriculture d'oasis des pays méditerranéens, 1993)
Egypt is at the second place in the world concerning the production of dates. The date palm tree is also present in all the cultivated areas of the country. However, a new policy for the development of the date palm sector has to be established to face the future needs in relation to the demographic growth.
Journées Internationales d'Elche sur le Palmier Dattier dans L'Agriculture d'Oasis des Pays Méditerranéens, 25-27 Apr 1995, Elche (Spain)